Cabazitaxel-Loaded Nanoparticles Reduce the Invasiveness in Metastatic Prostate Cancer Cells: Beyond the Classical Taxane Function - Jana B. Lampe; Priyanka P. Desai; Amit K. Tripathi; Nirupama A. Sabnis; Zhe Chen; Amalendu P. Ranjan; Jamboor K. Vishwanatha (MDPI AG, 2023)
Bone-metastatic prostate cancer symbolizes the beginning of the later stages of the disease. We designed a cabazitaxel-loaded, poly (lactic-co-glycolic acid) (PLGA) nanoparticle using an emulsion-diffusion-evaporation technique. Bis (sulfosuccinimidyl) suberate (BS3) was non-covalently inserted into the nanoparticle as a linker for the conjugation of a bone-targeting moiety to the outside of the nanoparticle. We hypothesized that the nanoparticles would have the ability to inhibit the epithelial-to-mesenchymal transition (EMT), invasion, and migration in prostate cancer cells. Targeted, cabazitaxel-loaded nanoparticles attenuated the EMT marker, Vimentin, and led to an increased E-cadherin expression. These changes impart epithelial characteristics and inhibit invasive properties in cancer progression. Consequently, progression to distant sites is also mitigated. We observed the reduction of phosphorylated Src at tyrosine 416, along with increased expression of phosphorylated cofilin at serine 3. These changes could affect migration and invasion pathways in cancer cells. Both increased p-120 catenin and inhibition in IL-8 expression were seen in targeted, cabazitaxel-loaded nanoparticles. Overall, our data show that the targeted, cabazitaxel-loaded nanoparticles can act as a promising treatment for metastatic prostate cancer by inhibiting EMT, invasion, and migration, in prostate cancer cells.